Cultivating Emotional Granularity - Wilson-Mendenhall, Christine D.; Dunne, John D. (Frontiers in Psychology, 2021)
An emerging focus in affective science is the expertise that underlies healthy emotionality. A growing literature highlights emotional granularity – the ability to make fine-grained distinctions in one’s affective feelings – as an important skill. Cross-sectional evidence indicating the benefits of emotional granularity raises the question of how emotional granularity might be intentionally cultivated through training. To address this question, we present shared theoretical features of centuries-old Buddhist philosophy and modern constructionist theory that motivate the hypothesis that contemplative practices may improve granularity. We then examine the specific mindfulness-style practices originating in Buddhist traditions that are hypothesized to bolster granularity. We conclude with future directions to empirically test whether emotional granularity can be intentionally cultivated.